Implanting Islamic Values in the Digital Age: Optimizing Digital Literacy in PAI Learning at Madrasah Ibtidaiyah - Qadir Audah, Abdullah; Subakri, Subakri; Muhith, Abdul; Rodliyah, St (Program Studi PGMI, 2025)
This study aims to examine how Islamic values can be implanted in Islamic Religious Education (PAI) learning through the optimization of digital literacy at MI Raudlatul Mutaalimin. Employing a qualitative approach with observations, interviews, and documentation, data were collected from teachers, students, and parents. The findings reveal that integrating digital media into PAI learning enhances moral awareness, digital literacy skills, and active student participation. However, challenges arise concerning technology use outside the classroom, requiring stronger collaboration between schools and families to establish a robust digital moral ecosystem. The study recommends strengthening teacher training, improving infrastructure, and increasing parental involvement to sustain Islamic value education in the digital era. These findings provide a foundation for developing an adaptive PAI learning model responsive to technological advances and future learners’ needs.